2015
DOI: 10.1111/dmcn.12788
|View full text |Cite
|
Sign up to set email alerts
|

The meaning of leisure for children and young people with physical disabilities: a systematic evidence synthesis

Abstract: Aim Participation in leisure has known health benefits. Children and young people (CYP) with physical disabilities demonstrate reduced participation in leisure. To facilitate their meaningful participation, one must understand what leisure means to CYP. The aim of this study was to systematically synthesize evidence from qualitative studies on the meaning of leisure for CYP with physical disabilities. Methods CINAHL, MEDLINE, AMED, EMBASE, PsycINFO, and ERIC were searched periodically from January 2012 until M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 53 publications
6
52
0
7
Order By: Relevance
“…Current developmental theories and models emphasise the importance of understanding the social context of children and the reciprocal nature of child-environment interactions [7, 8]. Similarly, two recently published reviews of leisure participation describe the central role of social contexts in creating meaningful experiences for children and youth with disabilities [9, 10]. However, there is limited exploration of other aspects of context in participation literature [11].…”
Section: Introductionmentioning
confidence: 99%
“…Current developmental theories and models emphasise the importance of understanding the social context of children and the reciprocal nature of child-environment interactions [7, 8]. Similarly, two recently published reviews of leisure participation describe the central role of social contexts in creating meaningful experiences for children and youth with disabilities [9, 10]. However, there is limited exploration of other aspects of context in participation literature [11].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has also demonstrated that preferences are an important predictor of participation in leisure . Because leisure participation is reported to provide fulfilment, friendship, and a sense of belonging, it is also an important avenue for development of self‐determination …”
mentioning
confidence: 99%
“…Optimal wellbeing and social participation in youth with NMD who are NIV users is possible, though published accounts are of single cases only 16 . As social connectedness with peers with similar life experiences is a powerful enhancer of physical and mental wellbeing in other groups living with disability 65,66 , the low scores in QoL leisure and social participation domains for youth with NMD across studies sourced in this review are of concern.…”
Section: Social Participationmentioning
confidence: 99%
“…This is surprising, given social participation is an identified priority in youth with NMD 15 and the value of social connectedness to long term health and wellbeing is known 65,77 . Future longitudinal research utilising standardised measures to describe the social worlds of adolescents growing up with progressive, chronic illness is necessary to aid deeper understanding of how health care supports and interventions impact on adolescents' short and long term wellbeing 78 .…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%